Freezing of Speech Single Questionnaire as a Screening Tool for Cognitive Dysfunction in Patients With Dementia With Lewy Bodies - Chiu, Pai-Yi; Hung, Guang-Uei; Wei, Cheng-Yu; Tzeng, Ray-Chang; Pai, Ming-Chyi (Frontiers in Aging Neuroscience, 2020)
Introduction: Freezing phenomenon is a striking feature of Parkinson’s disease. However, it has never been studied in people with dementia with Lewy bodies (DLB). We designed a freezing of speech single questionnaire (FOSSQ) and investigated the frequency and association of freezing of speech (FOS) in patients with DLB and other dementia. Methods: This is a retrospective analysis of data from the project of history-based artificial intelligent computerized dementia diagnostic system. We compared the frequencies of FOS among non-demented (ND) participants, patients with Alzheimer’s disease (AD), vascular dementia (VaD), and DLB. Further, we explored the association factors of FOS in all the participants. Results: We enrolled 666 individuals with the following disease distribution: 190, ND; 230, AD; 183, VaD; and 63, DLB. Compared to individuals with ND (2.1%), patients with AD (6.1%) or VaD (18.0%), DLB (54.0%) showed a significantly higher frequency of positive FOS (all p < 0.001). The association factors of FOS were older age, more severe dementia, more severe motor dysfunction, fluctuating cognition, visual hallucinations, parkinsonism, rapid eye movement sleep behavior disorder, attention, mental manipulation, and language. Conclusions: Our study showed that the informant-based FOSSQ may be a practical screening tool for discriminating DLB from individuals with ND or other dementia. The FOSSQ can be applied in clinical practice as well as in the artificial intelligent platform.